Metabolic impairment of non-small cell lung cancers by mitochondrial HSPD1 targeting - Parma, Beatrice; Ramesh, Vignesh; Gollavilli, Paradesi Naidu; Siddiqui, Aarif; Pinna, Luisa; Schwab, Annemarie; Marschall, Sabine; Zhang, Shuman; Pilarsky, Christian; Napoli, Francesca; Volante, Marco; Urbanczyk, Sophia; et al. (Journal of Experimental & Clinical Cancer Research, 2021)
Background The identification of novel targets is of paramount importance to develop more effective drugs and improve the treatment of non-small cell lung cancer (NSCLC), the leading cause of cancer-related deaths worldwide. Since cells alter their metabolic rewiring during tumorigenesis and along cancer progression, targeting key metabolic players and metabolism-associated proteins represents a valuable approach with a high therapeutic potential. Metabolic fitness relies on the functionality of heat shock proteins (HSPs), molecular chaperones that facilitate the correct folding of metabolism enzymes and their assembly in macromolecular structures. Methods Gene fitness was determined by bioinformatics analysis from available datasets from genetic screenings. HSPD1 expression was evaluated by immunohistochemistry from formalin-fixed paraffin-embedded tissues from NSCLC patients. Real-time proliferation assays with and without cytotoxicity reagents, colony formation assays and cell cycle analyses were used to monitor growth and drug sensitivity of different NSCLC cells in vitro. In vivo growth was monitored with subcutaneous injections in immune-deficient mice. Cell metabolic activity was analyzed through extracellular metabolic flux analysis. Specific knockouts were introduced by CRISPR/Cas9. Results We show heat shock protein family D member 1 (HSPD1 or HSP60) as a survival gene ubiquitously expressed in NSCLC and associated with poor patients' prognosis. HSPD1 knockdown or its chemical disruption by the small molecule KHS101 induces a drastic breakdown of oxidative phosphorylation, and suppresses cell proliferation both in vitro and in vivo. By combining drug profiling with transcriptomics and through a whole-genome CRISPR/Cas9 screen, we demonstrate that HSPD1-targeted anti-cancer effects are dependent on oxidative phosphorylation and validated molecular determinants of KHS101 sensitivity, in particular, the creatine-transporter SLC6A8 and the subunit of the cytochrome c oxidase complex COX5B. Conclusions These results highlight mitochondrial metabolism as an attractive target and HSPD1 as a potential theranostic marker for developing therapies to combat NSCLC.
CRIS-Team WoS Importer:2021-08-20

Polyol pathway-generated fructose is indispensable for growth and survival of non-small cell lung cancer - Schwab, Annemarie; Siddiqui, Mohammad Aarif; Ramesh, Vignesh; Gollavilli, Paradesi Naidu; Turtos, Adriana Martinez; Møller, Sarah Søgaard; Pinna, Luisa; Havelund, Jesper F.; Rømer, Anne Mette A.; Ersan, Pelin Gülizar; Parma, Beatrice; Marschall, Sabine; et al. (Cell Death and Differentiation, 2024)
Despite recent treatment advances, non-small cell lung cancer (NSCLC) remains one of the leading causes of cancer-related deaths worldwide, and therefore it necessitates the exploration of new therapy options. One commonly shared feature of malignant cells is their ability to hijack metabolic pathways to confer survival or proliferation. In this study, we highlight the importance of the polyol pathway (PP) in NSCLC metabolism. This pathway is solely responsible for metabolizing glucose to fructose based on the enzymatic activity of aldose reductase (AKR1B1) and sorbitol dehydrogenase (SORD). Via genetic and pharmacological manipulations, we reveal that PP activity is indispensable for NSCLC growth and survival in vitro and in murine xenograft models. Mechanistically, PP deficiency provokes multifactorial deficits, ranging from energetic breakdown and DNA damage, that ultimately trigger the induction of apoptosis. At the molecular level, this process is driven by pro-apoptotic JNK signaling and concomitant upregulation of the transcription factors c-Jun and ATF3. Moreover, we show that fructose, the PP end-product, as well as other non-glycolytic hexoses confer survival to cancer cells and resistance against chemotherapy via sustained NF-κB activity as well as an oxidative switch in metabolism. Given the detrimental consequence of PP gene targeting on growth and survival, we propose PP pathway interference as a viable therapeutic approach against NSCLC.
CRIS-Team Scopus Importer:2024-11-29

The role of miR-200b/c in balancing EMT and proliferation revealed by an activity reporter - Gollavilli, Paradesi Naidu; Parma, Beatrice; Siddiqui, Aarif; Yang, Hai; Ramesh, Vignesh; Napoli, Francesca; Schwab, Annemarie; Natesan, Ramakrishnan; Mielenz, Dirk; Asangani, Irfan Ahmed; Brabletz, Thomas; Pilarsky, Christian; et al. (Oncogene, 2021)
Since their discovery, microRNAs (miRNAs) have been widely studied in almost every aspect of biology and medicine, leading to the identification of important gene regulation circuits and cellular mechanisms. However, investigations are generally focused on the analysis of their downstream targets and biological functions in overexpression and knockdown approaches, while miRNAs endogenous levels and activity remain poorly understood. Here, we used the cellular plasticity-regulating process of epithelial-to-mesenchymal transition (EMT) as a model to show the efficacy of a fluorescent sensor to separate cells with distinct EMT signatures, based on miR-200b/c activity. The system was further combined with a CRISPR-Cas9 screening platform to unbiasedly identify miR-200b/c upstream regulating genes. The sensor allows to infer miRNAs fundamental biological properties, as profiling of sorted cells indicated miR-200b/c as a molecular switch between EMT differentiation and proliferation, and suggested a role for metabolic enzymes in miR-200/EMT regulation. Analysis of miRNAs endogenous levels and activity for in vitro and in vivo applications could lead to a better understanding of their biological role in physiology and disease.
CRIS-Team Scopus Importer:2021-03-19